Consumer Behavior and Marketing Mixed on Improving Decision-Making for Birth Delivery with Quality of Delivery Services as Variable Intervening - Wijayanti, Wijayanti; Supriyantoro, Supriyantoro; Pamungkas, Rian Adi (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: Excellent service quality needs to get immediate attention in providing services in hospitals; for this reason, it is essential to improve service quality as a marketing strategy. Objective: This study aims to analyze the effect of consumer behavior and marketing mix on the decision to select a delivery setting at Kartika Pulo Mas Hospital. Method: The quantitative and cross-sectional study was conducted from October 2022 - November 2022. A total of 50 patients as respondents were involved. Result: The results showed that consumer behavior, marketing mix, and service quality significantly affected the decision to choose a place of delivery at Kartika Pulo Mas Hospital. Conclusion: In conclusion, consumer behavior and marketing mix significantly affect decision-making in choosing a place of delivery at Kartika Pulo Mas Hospital, with the quality of delivery services as an intervening variable. Recommendation: The findings are input for hospital management to develop marketing strategies to improve consumer behavior in the form of consumer trust and also improve the marketing mix and quality of delivery services. Thereby, decision-making in choosing a place of delivery could improve